Review of Artemis Yagou, ed., Technology, Novelty, and Luxury - Markaki, Krystallia (Historein, 2024)
Review of Artemis Yagou, ed., Technology, Novelty, and Luxury (=Deutsches Museum Studies 12). Munich: Deutsches Museum, 2022. 118 pp.